2021
DOI: 10.1101/2021.02.28.433261
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HNF4α isoforms regulate the circadian balance between carbohydrate and lipid metabolism in the liver

Abstract: Hepatocyte Nuclear Factor 4α (HNF4α), a master regulator of hepatocyte differentiation, is regulated by two promoters (P1 and P2). P1-HNF4α is the major isoform in the adult liver while P2-HNF4α is thought to be expressed only in fetal liver and liver cancer. Here, we show that P2-HNF4α is expressed at ZT9 and ZT21 in the normal adult liver and orchestrates a distinct transcriptome and metabolome via unique chromatin and protein-protein interactions. We demonstrate that while P1-HNF4α drives gluconeogenesis, P… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 77 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…The fetal HNF4A isoforms lacking the N-terminal activation domain AF-1 relative to the adult isoforms are specifically expressed in the embryonic liver and diseased liver. They occupy much the same set of genome loci as the adult isoforms do yet exhibit a lower transcriptional activity 35,36 . We found that ectopically expressing the fetal isoform HNF4A8 induced tissue-specific BMAL1 binding likewise (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The fetal HNF4A isoforms lacking the N-terminal activation domain AF-1 relative to the adult isoforms are specifically expressed in the embryonic liver and diseased liver. They occupy much the same set of genome loci as the adult isoforms do yet exhibit a lower transcriptional activity 35,36 . We found that ectopically expressing the fetal isoform HNF4A8 induced tissue-specific BMAL1 binding likewise (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately, HNF4a is one of the most abundant transcription factors in the liver; the initial purification of HNF4a required only a 5000 to 10,000-fold enrichment (24). On the RNA level, HNF4a expression far surpasses that of all the other liverenriched transcription factors (HNF1, C/EBP, HNF3, HNF6), all other nuclear receptors, and even TATA binding protein and RNA polymerase (75). As it turns out, the moniker of "master regulator of liver-specific gene expression" does indeed seem to be appropriate.…”
Section: Hnf4a: Master Regulator Of Liverspecific Gene Expressionmentioning
confidence: 99%
“…Recent work from the Sladek group showed that mice with exclusive expressions of HNF4α-P1 and P2 have physiological role in normal adult liver. HNF4α-P1 regulates gluconeogenesis whereas HNF4α-P2 regulates ketogenesis in an adult liver in a circadian fashion [8].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…HNF4α-P1 regulates gluconeogenesis, whereas HNF4α-P2 regulates ketogenesis in an adult liver in a circadian fashion. 8 HNF4α has classic nuclear receptor A-F modular structure domains. 9 It consists of the activation functions (AF)-1 and AF-2, which activate transcription in a cell-type independent manner, and a DNA-binding domain, a ligand-binding do-main, and an activity repressor domain.…”
mentioning
confidence: 99%